Constraining Mountain Streamflow Constituents by Integrating Citizen Scientist Acquired Geochemical Samples and Sentinel‐1 SAR Wet Snow Time‐Series for the Shimshal Catchment in the Karakoram Mountains of Pakistan. Issue 3 (16th March 2023) - Lund, Jewell; Forster, Richard R.; Jameel, Yusuf; Rupper, Summer B.; Deeb, Elias J.; Dars, Ghulam Hussain; Zaheer, Azhar; Ali, Masood; Ghafoor, Abdul; Khan, Garee; Arfan, Muhammad; Liston, Glen E.; et al.
Abstract: Upper Indus Basin (UIB) streamflow originates largely from glacier and snow melt in the upstream Himalaya, Karakoram, and Hindu Kush mountain ranges and is extremely vulnerable because of its projected climate changes, dense populations, and hydropolitical tensions. Accurate knowledge of streamflow constituents is required for resilient water resources management; this is precluded by a paucity of measurement as well as climatological and topographic complexity. Here we integrate citizen scientist acquired geochemical samples, collected from October 2018 through September 2019 in the Shimshal watershed of the Karakoram Mountains of Pakistan, with Sentinel‐1 (S1) synthetic aperture radar (SAR)‐derived wet snow maps, to better understand streamflow constituents for the high altitude and heavily glaciated catchment. We use Bayesian end‐member mixture analysis to separate river flows into baseflow and meltwater constituents, using fixed and time‐variant melt end‐member values. We compare river hydrograph separation results with S1 wet snow time series maps for the same timeframe. We then utilize S1 imagery to inform end‐member mixture analysis to separate meltwaters into snow and glacier melt. For the Shimshal catchment, we find that about 85% of annual river flows are derived from snow and glacier melt; 45% of annual flows are derived from snow melt and 40% glacier melt. Engaged and committed citizen scientists enabled geochemical sample collection and analysis on a significant temporal and spatial scale. In the future, co‐produced knowledge that both implements local expertise and that is also planned and utilized by diverse stakeholders may increase climatological awareness and resilience in the UIB. Plain Language Summary: The Indus River Basin is home to about 300 million people that rely on streamflow for their livelihoods. Streamflow in the Indus is largely derived from snow and glacier melt from upstream mountain ranges. As populations increase and climate changes, understanding the role of snow and glacier melt in Indus streamflow is important for water resources management. Because of the rugged and remote nature of these mountain ranges, these important factors are not well understood. In this study, we work with local citizens in the Karakoram Mountains of Pakistan, who collected water samples from October 2018 through September 2019. We analyze these samples to better understand the role of meltwater in streamflow. We find that about 85% of streamflow is derived from snow and glacier meltwater. We also incorporate satellite remote sensing to better understand the role of snow versus glacier melt in streamflow. Snowmelt contributes 45% to streamflow; glacier melt contributes 40%. Improved knowledge of the role of snow and glacier melt in streamflow is important for sustainable water resources management in an area that is extremely vulnerable to water scarcity. Working with citizen scientists may improve our understanding of important variables to understand climate change in the region. Key Points: Citizen scientist acquired geochemical tracers are integrated with Sentinel‐1 synthetic aperture radar remote sensing to examine streamflow constituents Meltwater provides about 85% of the annual hydrograph in the Shimshal catchment: 45% snowmelt and 40% glacier melt Co‐produced knowledge holds the potential to address challenges with sparse climatological measurement in remote and rugged terrain